Guardianship and Parental Connections: Connections and Departures in Jeremy Bentham's Account. (1st January 2011) - Cox, Brian E.
Abstract : This article follows an earlier assessment of Bentham's views on guardianship 1 that touched on but did not explore connections or departures between guardian-ward and parent-offspring relations, about which Bentham was not as precise as he might have been. Further, he added complexity to the issue by describing parents as occupying dual roles: guardians and 'masters' (employers) of their own offspring. These relations are now considered, on the one hand, in the wider context of 'special relations' and 'duties' and, on the other hand, alongside some appreciation of Bentham's personal perspectives. However, the main object of the present article is to assess similarities and differences between parents and guardians in legal, status and functional terms. It uses the profile of guardian-ward relations provided by the previous article 2 as a benchmark. The article concludes by affirming that 'being a parent' and 'being a guardian' have quite different meanings.